Pengaruh Manfaat Penggunaan, Kemudahan Penggunaan, dan Keamanan Transaksi terhadap Minat Menggunakan Quick Response Code Indonesian Standard (QRIS) (Studi Pada Pelaku UMKM di Kecamatan Buleleng): (Studi Pada Pelaku UMKM di Kecamatan Buleleng) - Andriyani, Putu Sila; Julianto, I Putu; Vijaya, Diota Prameswari (Universitas Pendidikan Ganesha, 2025)
This study aims to test and analyze the effect of benefits of use, ease of use, and transaction security on the interest in using QRIS by MSMEs in Buleleng Subdistrict. This type of research is quantitative research with a causal approach and research instruments in the form of questionnaires. The population in this study were all MSMEs in Buleleng Subdistrict. The sampling technique used the simple random sampling method. The research sample consisted of 190 MSME actors in Buleleng Subdistrict, calculated using the Slovin formula. This study uses multiple regression analysis with the help of SPSS Statistics 18 software. The results of this study indicate that 1) benefits of use have a positive and significant effect on the interest of MSMEs in using QRIS; 2) ease of use has a positive and significant effect on the interest of MSMEs in using QRIS; 3) transaction security has a positive and significant effect on the interest of MSMEs in using QRIS; 4) Simultaneously, all independent variables have a significant effect on the interest of MSME actors in using QRIS.